PENGARUH KNOWLEDGE SHARING, KEPERCAYAAN DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI - Masni Masni; Ansir Ansir; Sinarwati Sinarwati (Pascasarjana Universitas Halu Oleo, 2018)
This study aims to examine and analyze empirically the Effects of Knowledge Sharing, Trust and Work Culture on Employee Performance at the UHO Rector. The population in this study were all the number of employees in the field of staffing UHO Rector as many as 65 people, and all were sampled. The analysis uses multiple linear regression analysis.The results showed that: (1) Knowledge sharing, trust and work culture had a positive and significant effect on the performance of employees at the UHO Rector. (2) Knowledge sharing has a positive and significant effect on the performance of employees at the UHO Rector. (3) Trust has a positive and significant effect on the performance of employees at the UHO Rector. (4) Work culture has a positive and significant effect on employee performance. Changes in work culture are positive and tangible in improving employee performance.Keywords: knowledge sharing, trust, work culture and employee performance